2019
DOI: 10.1016/j.radi.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Radiographers' perceptions of the barriers and enablers to effective smoking cessation support

Abstract: Therapeutic Radiographers' perceptions of the barriers and enablers to effective smoking cessation support. AbstractHighlights  Therapeutic Radiographers show desire for improvements within their practice  Therapeutic Radiographers fear upsetting the patient during smoking cessation advice  Therapeutic Radiographers worry about damaging the therapeutic relationship  There is a clear need for a Therapeutic Radiographer specific training package

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“… 15 28 37 In one qualitative study a key facilitator reported among TRs in delivering smoking cessation support to patients was knowledge of the link between smoking and toxicity. 28 Another qualitative study that explored allied health professionals’ views regarding the provision of dietary advice to patients, highlighted that TRs report giving dietary advice to help counteract the side effects of radiotherapy. 37 Additionally, in our study, if TRs did provide dietary advice, this tended to be general advice rather than cancer-specific advice on healthy eating.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 15 28 37 In one qualitative study a key facilitator reported among TRs in delivering smoking cessation support to patients was knowledge of the link between smoking and toxicity. 28 Another qualitative study that explored allied health professionals’ views regarding the provision of dietary advice to patients, highlighted that TRs report giving dietary advice to help counteract the side effects of radiotherapy. 37 Additionally, in our study, if TRs did provide dietary advice, this tended to be general advice rather than cancer-specific advice on healthy eating.…”
Section: Discussionmentioning
confidence: 99%
“…15 Similarly, focus group interviews with 38 TRs identified that lack of knowledge and training were barriers to the provision of smoking cessation advice. 28 Challenges remain in translating behaviour change interventions into existing care pathways and practices in a way that is appropriate for use by health professionals. 29 Understanding TRs' practices, and what support they need in delivering advice on the topics of physical activity, healthy eating, alcohol intake, smoking and weight management could inform the development of interventions that will enable TRs' in delivering advice on improving health behaviours to those LWBC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whilst research shows that some oncology healthcare professionals (HCPs) offer guidance to oncology patients on healthy lifestyle changes, provision remains suboptimal [2][3][4][5][6]. In the UK, a qualitative study among ten oncology HCPs and sixteen prostate cancer patients found that HCPs do not routinely provide advice on diet and PA to men diagnosed with prostate cancer, with some patients unable to recall receiving any advice on diet or PA from their healthcare team [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, a qualitative study among ten oncology HCPs and sixteen prostate cancer patients found that HCPs do not routinely provide advice on diet and PA to men diagnosed with prostate cancer, with some patients unable to recall receiving any advice on diet or PA from their healthcare team [3]. Reported barriers among oncology HCPs in delivering advice on health behaviours include believing that giving advice is not part of their role, lack of support and time, lack of guidelines, lack of knowledge of the evidence base, and concerns around seeming to blame the patient [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%